2015
DOI: 10.1134/s0012496615060022
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in regulation of leukocyte migration into the heart tissue in vitro

Abstract: Characteristics of leukocyte migration have been studied during the incubation of the right and left ventricles of rat heart explants in autologous blood plasma. Within the first 60 min, the leukocyte amount in the medium increases. Moreover, it is associated with cell release from the heart tissue. During further incubation, the cell release decreases; after 3 h of incubation, the cells begin to migrate back into the heart tissue. However, neutrophil migration does not change. Sodium nitrite, being a donor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Interestingly, it has been reported that NO induces PECAM‐1, VLA‐4 and Mac‐1 expression, thus accelerating the transendothelial migration of neutrophils, Also, animals treated with iNOS inhibitors or iNOS − / − mice show reduced neutrophil migration induced by carrageenan . However, the effects of NO are contradictory, suggesting that the importance of iNOS in modulating leucocyte recruitment can vary according to the type of inflammatory response . We can hypothesise that AEEm and Fr20 can be inhibiting NO production, which can be contributing to reducing inflammation signs on the vascular system and leucocyte migration into inflammatory site.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, it has been reported that NO induces PECAM‐1, VLA‐4 and Mac‐1 expression, thus accelerating the transendothelial migration of neutrophils, Also, animals treated with iNOS inhibitors or iNOS − / − mice show reduced neutrophil migration induced by carrageenan . However, the effects of NO are contradictory, suggesting that the importance of iNOS in modulating leucocyte recruitment can vary according to the type of inflammatory response . We can hypothesise that AEEm and Fr20 can be inhibiting NO production, which can be contributing to reducing inflammation signs on the vascular system and leucocyte migration into inflammatory site.…”
Section: Discussionmentioning
confidence: 94%
“…[48] However, the effects of NO are contradictory, suggesting that the importance of iNOS in modulating leucocyte recruitment can vary according to the type of inflammatory response. [45,48] We can hypothesise that AEEm and Fr20 can be inhibiting NO production, which can be contributing to reducing inflammation signs on the vascular system and leucocyte migration into inflammatory site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation